Anticonvulsant evaluation of 2-pyrazolines carrying naphthyl moiety: An insight into synthesis and molecular docking study - Birjees Nusrat; Nadeem Siddiqui; Meeta Sahu; Mohd. Javed Naim; Mohammad Shahar Yar; Ruhi Ali; Alam Ozair
A series of N-substituted-3-(napthalen-2-yl)-5-substituted phenyl-4,5-dihydropyrazole-1-carbothioamide derivatives (4a-n) were synthesized with the view of structural requirements of pharmacophore for potential anticonvulsant agents. The synthesized compounds were assayed intraperitoneally (i.p.) and subcutaneously (s.c.) in mice against seizures induced by MES and scPTZ methods, respectively.Neurologic deficit was evaluated by rotarod method. Among the tested compounds, 4g, 4i, 4j and 4n emerged as the most active molecule in the MES model at a dose of 30 mg/kg at 0.5h comparable to standardscarbamazepine and phenytoin. In the scPTZ test,4e and 4l were found to be most active compounds at the lowest dose of 30 mg/kg at 0.5h, in the management of the convulsive disorder. Molecular docking studies of the titled compounds were also donewith 3D crystal structure of human cytosolic branched chain amino transferase (hBCATc) enzyme and compound 4e was found to have five hydrogen bond interactions with the most important active site residues.In neurotoxicity studies, except compounds 4b, 4c, 4h and 4k, rest of the compounds showed no sign of toxicity.